Value in nature and the nature of value - Rolston, Holmes, 1932-2025, author; Cambridge University Press, publisher (Colorado State University. Libraries, 1994)
Value is often thought not to exist in wild nature; it is bestowed on nature by human preferences. This prevailing account is too anthropocentric. In nature, animals value their lives; they too can have their preferences satisfied. Plants have vital needs. Species are historical forms of life defended over generations. Ecosystems are "able to generate value," as occurs with the evolution and ecological support of organisms, animals, and humans. Earth, taken as earth, dirt, seems of little intrinsic value; but Earth, the home planet, is systemically valuable, the ground of all value.
Invited conference address at the Royal Society of Philosophy Annual Conference, University of Wales, Cardiff, July 18-21, 1993.
Keywords: humans; environmental ethics; species; organisms; ecosystems; environmental values; philosophy of nature